STP Best Practices for Evaluating Clinical Pathology in Pharmaceutical Recovery Studies. (February 2016) - Tomlinson, Lindsay; Ramaiah, Lila; Tripathi, Niraj K.; Barlow, Valerie G.; Vitsky, Allison; Poitout-Belissent, Florence M.; Bounous, Denise I.; Ennulat, Daniela
The Society of Toxicologic Pathology formed a working group in collaboration with the American Society for Veterinary Clinical Pathology to provide recommendations for the appropriate inclusion of clinical pathology evaluation in recovery arms of nonclinical toxicity studies but not on when to perform recovery studies. Evaluation of the recovery of clinical pathology findings is not required routinely but provides useful information on risk assessment in nonclinical toxicity studies and is recommended when the ability of the organ to recover is uncertain. The study design generally requires inclusion of concurrent controls to separate procedure-related changes from test article–related changes, but return of clinical pathology values toward baseline may be sufficient in some cases. Evaluation of either a select or full panel of standard hematology, coagulation, and serum and urine chemistry biomarkers can be scientifically justified. It is also acceptable to redesignate dosing phase animals to the recovery phase or vice versa to optimize data interpretation. Assessment of delayed toxicity during the recovery phase is not required but may be appropriate in development programs with unique concerns. Evaluation of the recovery of clinical pathology data for vaccine development is required and, for efficacy markers, is recommended if it furthers pharmacologic understanding.